1983
DOI: 10.1111/j.1751-1097.1983.tb03356.x
|View full text |Cite
|
Sign up to set email alerts
|

SITE‐SELECTION SPECTROSCOPY OF CHLOROPHYLL b IN MEMBRANES OF LECITHIN VESICLES AND IN OTHER SOLVENTS

Abstract: Abstract— Site‐selection fluorescence spectra of chlorophyll b in membranes of lecithin vesicles and in the solvents ethanol, n‐butanol, n‐butyl acetate, 2‐methyl tetrahydrofuran and toluene are presented. The spectra in vesicles display zero‐phonon lines as pronounced as those in the best organic glasses. The characteristics of the distributions of O—O transition energies and of the electron‐phonon couplings allow to infer the position of the chlorophyll molecule in the membrane of vesicles. It is thus found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It was suggested that Chl molecules are located just below the membrane surface [213]. The spectroscopic and fluorescence data point to the polar environment of Chl tetrapyrrol macroring rather than to its direct contact with the aqueous phase [214,215]. Most likely this polar environment is formed by the domains of the ester groups of lecithin molecules.…”
Section: Chlorophyll-containing Membranesmentioning
confidence: 95%
“…It was suggested that Chl molecules are located just below the membrane surface [213]. The spectroscopic and fluorescence data point to the polar environment of Chl tetrapyrrol macroring rather than to its direct contact with the aqueous phase [214,215]. Most likely this polar environment is formed by the domains of the ester groups of lecithin molecules.…”
Section: Chlorophyll-containing Membranesmentioning
confidence: 95%
“…A possible explanation for the increasing kqm-values above n = 4 is that the average positions of the bipyridinium rings of the viologens become increasingly closer to the interior of the membrane with increasing n from n = 5 to 8. This change in location would bring the electron-accepting parts of the molecules closer to the chlorin rings of the Chl molecules, which are probably oriented with the rings located close to the membrane-water interface, but folded back towards the interior of the membrane (Oettmeier et al, 1976;Funfschilling et al, 1983;Ford and Tollin, 1984). The great sensitivity of electron transfer reactions to the distance between the donor and acceptor (Miller et al, 1982) could then account for the 20-fold increase in k," of octyl viologen relative to that of methyl, ethyl, propyl, and butyl viologens.…”
Section: Triplet Quenchingmentioning
confidence: 99%
“…This agrees with the expectation that the porphyrin cation is held in a rather narrow energetic well in the polar region of the bilayer. Both energy calculations (Brasseur et al, 1984) and site selection spectroscopy (Funfschilling and Walz, 1983) place the ring of chl a in the polar region of the bilayer. The variable Ameasures the probability that a donor species is at the closest distance to P+, and should be proportional to the added donor concentration since no saturation is observed (see below).…”
Section: Decay Of Photovoltage As a Function Of Ferricyanide And Ferrmentioning
confidence: 99%